2014
DOI: 10.1002/iid3.22
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study showing differences in glycosylation patterns of IgG subclasses induced by pneumococcal, meningococcal, and two types of influenza vaccines

Abstract: The presence of a carbohydrate moiety on asparagine 297 in the Fc part of an IgG molecule is essential for its effector functions and thus influences its vaccine protective effect. Detailed structural carbohydrate analysis of vaccine induced IgGs is therefore of interest as this knowledge can prove valuable in vaccine research and design and when optimizing vaccine schedules. In order to better understand and exploit the protective potential of IgG antibodies, we carried out a pilot study; collecting serum or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 64 publications
4
29
0
Order By: Relevance
“…Statistical analyses were performed using paired t-test (comparing glycosylation-levels in first and subsequent available pregnancies) and Kruskal Wallis test (comparing subsequent pregnancies after the index pregnancy). during pregnancy and decrease after delivery (van de Geijn et al, 2009) (and this study) and is transiently increased after immunization (Selman et al, 2012a;Vestrheim et al, 2014). Interestingly, we found that anti-HPA-1a IgG1-Fc galactosylation remained high after delivery, suggesting that the antigen-specific IgG1 galactosylation is less influenced by systemic changes induced by pregnancy.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Statistical analyses were performed using paired t-test (comparing glycosylation-levels in first and subsequent available pregnancies) and Kruskal Wallis test (comparing subsequent pregnancies after the index pregnancy). during pregnancy and decrease after delivery (van de Geijn et al, 2009) (and this study) and is transiently increased after immunization (Selman et al, 2012a;Vestrheim et al, 2014). Interestingly, we found that anti-HPA-1a IgG1-Fc galactosylation remained high after delivery, suggesting that the antigen-specific IgG1 galactosylation is less influenced by systemic changes induced by pregnancy.…”
Section: Discussionsupporting
confidence: 50%
“…For example, vaccination shows transient increases in IgG galactosylation and sialylation while fucosylation is stable and remains high (Selman et al, 2012a;Bakovic et al, 2013;Vestrheim et al, 2014). The level of galactosylated IgG changes with age, disease and pregnancy (Malhotra et al, 1995;Pucic et al, 2011;Bakovic et al, 2013).…”
mentioning
confidence: 97%
“…The use of antigen-specific Ab glycan profiles would be particularly attractive clinical correlates given their ease of interrogation (Mahan et al, 2015). Importantly, because vaccination generates Ab profiles distinct from natural infection (Mahan et al, 2016; Vestrheim et al, 2014), antigen-specific Ab glycan profiles may provide diagnostic value even in an immunized population. Moreover, differences in glycosylation patterns observed in individuals with TB as compared to other chronic infections such as HIV (Supplemental Figure 6) (Mahan et al, 2016) suggest that these changes are not necessarily simply representative of a non-specific inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that IgG1‐responses against platelet antigens and RhD on RBCs can be particularly skewed towards IgG with low core‐fucosylation (Wuhrer et al , ; Kapur et al , ; Sonneveld et al , ), a feature that has only previously been described for anti‐human immunodeficiency virus (HIV) antibodies, but never for any other immune response (Ackerman et al , ). This is reflected in total serum IgG‐Fc having ~94% fucose on the glycopeptide level (Selman et al , ; Fokkink et al , ; Vestrheim et al , ). The lowered core‐fucosylation of both anti‐D and anti‐Human Platelet Antigen (HPA)‐1a platelet antibodies correlated with severity of disease in patients with HDFN or fetal or neonatal alloimmune thrombocytopenia (FNAIT) (Kapur et al , ).…”
mentioning
confidence: 99%